DEVELOPMENT OF LIBRARIAN PRACTICES IN CREATION PROCESSES OF UNIVERSITIES SCIENTIFIC POTENTIALS - Myrhorodska, Alla I.; Savelieva, Olena A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Development of library practices at creation processes of Universities scientific potentials, information analytics, bibliometric research on the example of the libraries in USA, Canada, Australia and Ukraine was considered. Actual performance of the Scientific and Technical Library of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT) − focused on support of scientific research were presented.